The Mediating Role of Shame Proneness and Defensive Communication in the Relationship between Childhood Trauma and Partner Criticism Sensitivity - Majlesi, Neda; AbdolaliSarbandi, Atena; Naqavi, Maryam (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to examine whether shame proneness and defensive communication mediate the relationship between childhood trauma and partner criticism sensitivity in adults. Methods and Materials: This study employed a quantitative, cross-sectional, correlational design using structural equation modeling. The statistical population consisted of adults residing in Tehran, Iran, who were currently in a romantic relationship or had experienced one within the past year. A total of 412 participants were selected through convenience sampling. Data were collected using standardized self-report instruments, including the Childhood Trauma Questionnaire (CTQ), Test of Self-Conscious Affect (TOSCA) for measuring shame proneness, a Defensive Communication Scale, and the Perceived Criticism Sensitivity Scale. Data analysis was conducted using SPSS-27 for descriptive statistics and AMOS for structural equation modeling. Model fit indices and bootstrapping procedures were used to assess direct and indirect effects. Findings: The results of structural equation modeling indicated that childhood trauma had a significant positive effect on shame proneness (β = 0.51, p < 0.001), defensive communication (β = 0.29, p < 0.001), and partner criticism sensitivity (β = 0.17, p = 0.001). Shame proneness significantly predicted defensive communication (β = 0.38, p < 0.001) and partner criticism sensitivity (β = 0.34, p < 0.001), while defensive communication significantly predicted partner criticism sensitivity (β = 0.41, p < 0.001). Bootstrapping analysis confirmed significant indirect effects of childhood trauma on partner criticism sensitivity through shame proneness (β = 0.17), defensive communication (β = 0.12), and sequential mediation via both variables (β = 0.08), indicating partial mediation. The overall model demonstrated good fit (χ²/df = 2.41, CFI = 0.94, TLI = 0.93, NFI = 0.92, RMSEA = 0.058). Conclusion: The findings demonstrate that shame proneness and defensive communication serve as significant mediating mechanisms linking childhood trauma to partner criticism sensitivity.